Konstruksi Filantropi Kampung SDG'S (Sustainable Development Goals) Baznas Jember dalam Penguatan Ekonomi - Rahman, Fawait Syaiful (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
The purpose of this study is to describe the philanthropic construction of SDG's Village assisted by Baznas Jember and to determine the development of the implications of SDG's Village on the economy of the Jember community. The method used is qualitative, with the type of field research. The data collection method uses interviews, observation, and documentation techniques. The process of data analysis uses reduction, display, and conclusions. The data obtained is then tested for credibility through triangulation. The results showed that Baznas Jember was able to maximize the potential of people's philanthropic funds in the form of realization of superior programs for approximately 2017- 2027 through the SDG's Village forum. The SDG's village assisted by Baznas Jember can color the people of Jember district to join together to build a prosperous Jember through five SDG's Village programs, namely SDG's Smart Village, SDG's Healthy Village, SDG's Takwa Village, SDG's Islam Village, and SDG's Makmur Village. Baznas Jember through SDG's village assists underprivileged communities by including training on coffee production, empowering empty environments with catfish cultivation, and hydroponic vegetable farming.